Flexible wearable devices for intelligent health monitoring. Issue 5 (12th September 2022) - Dai, Baoying; Gao, Chenchen; Xie, Yannan
Abstract: Profited from the rapid development of flexible skin‐like electronic materials and artificial intelligent technology, remarkable achievements have been witnessed in wearable health monitoring devices in recent years. The wearable intelligent systems featured with tailored structures and compositions as well as enriched functions enable human beings to access to next‐generation closed‐loop platform for early disease prevention and diagnosis. In this context, this mini‐review focuses on the recent progress and applications of flexible wearable intelligent health monitoring devices. Specifically, the basic sensing mechanisms and corresponding property requirements for wearable healthcare devices are examined firstly. Secondly, the versatile applications of advanced wearable devices for detecting temperature, heart rate, blood pressure and glucose are scrutinized exclusively. Finally, a brief summary is presented accompanying with future outlook in terms of material preparation, mechanism development and integration design of monitoring systems. This manuscript is expected to provide critical guidelines to those working in skin‐like electronics, flexible sensors, wearable intelligent devices, health monitoring and other related disciplines, especially for the beginners. Abstract : Flexible wearable sensors with good biocompatibility, breathability, flexibility, sensibility, accuracy and durability show great prospects in early prevention, intervention, diagnosis and treatment of diseases. The devices can utilize piezoelectric, piezoresistive, triboelectric, capacitive or magnetoelastic effects for blood pressure monitoring, thermoelectric, photothermal or pyroelectric effects for temperature monitoring, and electrocatalytic, electrochemical or photoelectrochemical mechanisms for glucose monitoring.